2019
DOI: 10.1021/acsptsci.8b00048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pirin as a Molecular Target of the CCG-1423/CCG-203971 Series of Antifibrotic and Antimetastatic Compounds

Abstract: A series of compounds (including CCG-1423 and CCG-203971) discovered through an MRTF/SRF-dependent luciferase screen has shown remarkable efficacy in a variety of in vitro and in vivo models, including significant reduction of melanoma metastasis and bleomycin-induced fibrosis. Although these compounds are efficacious in these disease models, the molecular target is unknown. Here, we describe affinity isolation-based target identification efforts which yielded pirin, an iron-dependent cotranscription factor, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…To investigate the role of the MRTF/SRF pathway in the regulation of FGFR1 in hMSCs, we inhibited the pathway using CCG203971 31 , 32 . Indeed, in both hMSCs and fibroblasts, inhibition of the MRTF/SRF pathway reduced FGFR1 expression by 60 ± 7% ( p < 0.01) and 62 ± 3% ( p < 0.01), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the role of the MRTF/SRF pathway in the regulation of FGFR1 in hMSCs, we inhibited the pathway using CCG203971 31 , 32 . Indeed, in both hMSCs and fibroblasts, inhibition of the MRTF/SRF pathway reduced FGFR1 expression by 60 ± 7% ( p < 0.01) and 62 ± 3% ( p < 0.01), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there is consistent evidence that bisamide modulates the expression of the transcription factor HSF1 and subsequently inhibits the migration of human melanoma cells WM266.4; however, Pirin participation remains unclear [71]. In light of these findings, it was recently demonstrated that both CCG-222740 and CCG-257081, which are compounds structurally similar to CCT251236 and possible inhibitors of metastatic and fibrotic signals, are also able to bind to Pirin [32]. Moreover, they show that such CCG compounds may disrupt Pirin expression, and subsequently interfere with MRTF/SRF/DNA signaling, which has been associated with melanoma metastasis [32].…”
Section: Skin Cancermentioning
confidence: 99%
“…Additionally, Pirin has been reported as a molecular target of metastatic suppressors. However, the Pirin activity in cancer development remains a novel area of research [32]. The following paragraphs summarize the interaction of Pirin with carcinogenic agents and its potential role in epithelial carcinogenesis.…”
Section: Role Of Pirin In Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of the MRTF/SRF pathway in the regulation of FGFR1 in hMSCs, we inhibited the pathway using CCG203971 [48,49] . Indeed, in both hMSCs and fibroblasts, inhibition of the MRTF/SRF pathway reduced FGFR1 expression by 59.6±7.0% (p<0,01) and 61.5±2.9% (p<0.01), respectively (Fig 5a, c).…”
Section: Actin-myosin and Mrtf/srf Pathway Regulate Fgfr1 Expressionmentioning
confidence: 99%